EMERGENCY OBSTETRICS CARE SERVICES IN DISTRICT NEELUM, AZAD JAMMU AND KASHMIR - Mateen, Abdul; Shaikh, Babar Tasneem; Kumar, Ramesh (Journal of Ayub Medical College Abbottabad, 2013)
Background: Globally 529,000 women die annually due to pregnancy related problems and in Pakistan alone this toll is about 35,000 deaths per annum. This situation is even more critical in the rural remote areas of Azad Jammu & Kashmir (AJK). The whole phenomenon needs a contextual assessment to ascertain the geographical, financial and socio cultural accessibility, and availability of EmOC services in order to generate fresh evidence for the decision makers and concerned stakeholders for improving these services. Methods: A cross-sectional study was conducted using a structured questionnaire with the women delivered in the last 15 days, whereas the geographical accessibility and availability of EmOC services were assessed by visiting EmOC facilities in the district Neelum of AJK. Results: Over a hundred women delivered in the last 15 days, participated in the study. Geographically, a central EmOC facility is far away and the terrain is hilly and dangerous. Women’s social status, education, husband’s employment and household income were found to have a significant association with the use of EmOC services. The health facilities audit showed that around 90% centres do not have a female medical officer appointed. Moreover, the state of the equipment, medicines and the basic utilities such as water, sanitation, and electricity are not satisfactory. Conclusion: Accessibility of EmOC services is poor in the district Neelum. Evidence on ground calls for organisational reforms at EmOC service delivery level as well as for long term planning in other sectors for improving socio-economic and education status of the women in Azad Jammu & Kashmir. Keywords: Emergency obstetrics care, reproductive health, health care